1993
DOI: 10.1007/bf01742195
|View full text |Cite
|
Sign up to set email alerts
|

Five years of strategic environmental assessment efforts at a research university: A case study of an organizational innovation

Abstract: This study examined the emergence and subsequent five-year history of "environmental scanning" at a large research university. Proponents of strategic approaches to management in organizations usually recommend environmental scanning as a necessary support for effective decision making. The technique seeks to build systematic understanding of the external environment of the organization, via ongoing reconnaissance of relevant developments in technology, the economy, the political and legal arenas, and the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Several later studies on higher education linked institutional culture with organizational success (Chaffee & Tierney, 1988;Peterson, Cameron, Jones, Mets, & Ettington, 1986). Further studies demonstrated the way that different cultures shaped various institutional functions including governance (Chaffee & Tierney, 1988), leadership (Birnbaum, 1988), and planning (Hearn, Clugston, & Heydinger, 1993;Leslie & Fretwell, 1996).…”
Section: Organizational Culturementioning
confidence: 98%
“…Several later studies on higher education linked institutional culture with organizational success (Chaffee & Tierney, 1988;Peterson, Cameron, Jones, Mets, & Ettington, 1986). Further studies demonstrated the way that different cultures shaped various institutional functions including governance (Chaffee & Tierney, 1988), leadership (Birnbaum, 1988), and planning (Hearn, Clugston, & Heydinger, 1993;Leslie & Fretwell, 1996).…”
Section: Organizational Culturementioning
confidence: 98%
“…Incentives for departments, colleges, staff and line administrative units are all important for successful implementation, but the financial, professional and personal incentives for individual faculty merit special attention (Hearn, Clugston and Heydinger 1993;Hearn 1996;Newman and Couturier 2001). How should institutions structure faculty salaries and resource contexts to create incentives for new revenue generation?…”
Section: Methodsmentioning
confidence: 99%
“…The book by George Keller, Academic Strategy, is an excellent example of this approach (Keller, 1983). Later authors started to work on organizational characteristics of universities and how these influence strategic planning (Chaffee, 1985;Chaffee, 1989;Dill, 1993a;Dill, 1994;Hearn, Clugston, and Heydinger, 1993;Keller, 1995;Peterson, 1997).…”
Section: Strategic Choicementioning
confidence: 99%